Propertius in Love : The Elegies - Propertius, Sextus (Book collections on Project MUSE., 2002)
These ardent, even obsessed, poems about erotic passion are among the brightest jewels in the crown of Latin literature. Written by Propertius, Rome's greatest poet of love, who was born around 50 b.c., a contemporary of Ovid, these elegies tell of Propertius' tormented relationship with a woman he calls "Cynthia." Their connection was sometimes blissful, more often agonizing, but as the poet came to recognize, it went beyond pride or shame to become the defining event of his life. Whether or not it was Propertius' explicit intention, these elegies extend our ideas of desire, and of the human condition itself.